2023
DOI: 10.1111/nph.19283
|View full text |Cite
|
Sign up to set email alerts
|

GlobalAMFungi: a global database of arbuscular mycorrhizal fungal occurrences from high‐throughput sequencing metabarcoding studies

Tomáš Větrovský,
Zuzana Kolaříková,
Clémentine Lepinay
et al.

Abstract: Summary Arbuscular mycorrhizal (AM) fungi are crucial mutualistic symbionts of the majority of plant species, with essential roles in plant nutrient uptake and stress mitigation. The importance of AM fungi in ecosystems contrasts with our limited understanding of the patterns of AM fungal biogeography and the environmental factors that drive those patterns. This article presents a release of a newly developed global AM fungal dataset (GlobalAMFungi database, https://globalamfungi.com) that aims to reduce this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 77 publications
3
11
0
Order By: Relevance
“…Additionally, all tree species associated with a large number of AM fungi simultaneously, leading to complex multispecies assemblages within roots. These results are in accordance with previous research that has shown that OTU diversity of rhizosphere samples is generally higher than that found in roots (Sheldrake et al 2018;Boeraeve et al 2019b;Větrovský et al 2023). This suggests that the regional pool of AM fungi from which the trees can select their partners, is larger than what eventually occurs in the roots and that the members of local communities are selected by passing through abiotic and biotic filters (Jumpponen and Egerton-Warburton 2005;Vályi et al 2016).…”
Section: Am Fungal Communities In Soil and Root Samplessupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, all tree species associated with a large number of AM fungi simultaneously, leading to complex multispecies assemblages within roots. These results are in accordance with previous research that has shown that OTU diversity of rhizosphere samples is generally higher than that found in roots (Sheldrake et al 2018;Boeraeve et al 2019b;Větrovský et al 2023). This suggests that the regional pool of AM fungi from which the trees can select their partners, is larger than what eventually occurs in the roots and that the members of local communities are selected by passing through abiotic and biotic filters (Jumpponen and Egerton-Warburton 2005;Vályi et al 2016).…”
Section: Am Fungal Communities In Soil and Root Samplessupporting
confidence: 92%
“…For example, VTX00069, the closest match in the MaarjAM database (Öpik et al 2010) to our most abundant OTU, has been found in a tropical forest in Panama (Husband et al 2002), savannah in Madagascar (Yamato et al 2009), agricultural land in subtropical Mexico (Alguacil et al 2008), a tropical mountain rainforest in Ecuador (Kottke et al 2008), and a tropical forest in French Polynesia (Davison et al 2018). The second most abundant OTU could not be matched with a virtual taxon in the MaarjAM database, but did match with a sequence in the GlobalAMFungi database (Větrovský et al 2023), which came from a cocoa plantation in Côte d'Ivoire (Rincón et al 2021). Also our third most abundant OTU matched with a virtual taxon from the MaarjAM database (VTX00132) and could be traced back to many of the aforementioned studies in (sub)tropical regions (Husband et al 2002;Yamato et al 2009;Davison et al 2018), although it has also been observed in several studies in temperate or Mediterranean regions (de Leon et al 2016;Davison et al 2018).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Their relative abundances were negatively correlated, suggesting an antagonistic relationship and competition for habitat occupancy. These two dominant OTUs are globally distributed in forest and grassland ecosystems, respectively (Větrovský et al 2023 ). According to the database, VTX00080 is equally distributed in roots (44.56%) and soils (44.3%), and more in forest (76.39%) than in cropland (18.44%) ecosystems; VTX00166 is more distributed in roots (66.25%) than in soils (28.84%), and equally distributed in grassland (39.27%) and forest (40.17%) ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Chimeric sequences and rare OTUs (less than 10 reads across all samples or detected in only one sample) were discarded. Representative sequences of the OTUs were BLASTed against Maarj AM (Öpik et al 2010 ), GlobalAMFungi (Větrovský et al 2023 ), and National Center for Biotechnology Information (NCBI) GenBank databases using the NCBI-blast-2.10.0 + program (Morgulis et al 2008 ) to discard non-Glomeromycotina OTUs. Taxa were assigned to OTUs based on the best matches to the abovementioned databases (query cover and percent identity > 95%), the consensus on AMF classification (Redecker et al 2013 ) was used to update the taxonomic affiliation of the OTUs, and the composition of the AMF communities was visualized at the genus level.…”
Section: Methodsmentioning
confidence: 99%